2022
DOI: 10.54300/422.974
|View full text |Cite
|
Sign up to set email alerts
|

How Do California Preschool Quality Ratings Relate to Children's Development?

Abstract: High-quality early learning has the potential to narrow disparities in children’s learning and development prior to kindergarten entry, particularly for children from families with low incomes and children who are multilingual learners. This study investigates the relationship between preschool quality and children’s learning and development from fall to spring of 1 school year through the analysis of child- and program-level data from approximately 70,000 children in California preschool programs. It suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Research demonstrates that high-quality ECE programs can support early learning and development for all children and may provide even greater benefits for children classified as DLLs (Sussman et al, 2022;Yazejian et al, 2015;Yoshikawa et al, 2013). However, a clear and consistent finding in the literature is that children classified as DLLs do not have the same access to high-quality programs as their monolingual peers (NASEM, 2017).…”
Section: Translating Research To Practice: Effective Early Education ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research demonstrates that high-quality ECE programs can support early learning and development for all children and may provide even greater benefits for children classified as DLLs (Sussman et al, 2022;Yazejian et al, 2015;Yoshikawa et al, 2013). However, a clear and consistent finding in the literature is that children classified as DLLs do not have the same access to high-quality programs as their monolingual peers (NASEM, 2017).…”
Section: Translating Research To Practice: Effective Early Education ...mentioning
confidence: 99%
“…The widths were set by the item parameters that account for knowledge and skills that emerge earlier or later in development and the time in-between the emergence of developmental skills and behaviors. Sussman et al (2021) used a classification accuracy approach to examine the agreement between a child's developmental level and each of their item levels for the five major DRDP domains. In a sample of 1.5 million assessments (with some children observed more than once), the authors found an average of 69% agreement between the developmental (domain) level and the item level.…”
Section: Pedagogically Relevant Assessment Scoresmentioning
confidence: 99%